1997
DOI: 10.1093/humrep/12.5.1073
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery in gynaecology: the first uterine pass effect

Abstract: The objective was to verify the hypothesis of a 'first uterine pass effect' or direct preferential vagina-to-uterus transport, suggested by the evidence of higher than expected uterine tissue concentrations after vaginal administration of progesterone; we used a human ex-vivo uterine perfusion model. A mixture of tritiated (3H) and unlabelled progesterone was applied to the cuff of vaginal tissue remaining attached to the cervix after hysterectomy. At the end of the perfusion period (up to 12 h), 3H and 14C ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(101 citation statements)
references
References 17 publications
2
93
1
5
Order By: Relevance
“…We studied a vaginal preparation of progesterone, at a dose of 400 mg twice daily, and it is possible that the results with this regimen are not generalizable to patients receiving other doses and preparations. However, we chose this route to deliver a greater proportion of the drug to the biologically relevant site (i.e., the uterus), 13,14 and the dose used (400 mg twice daily) represents a dose at the top end of the therapeutic window. 15 Some researchers have suggested that intramuscular preparations of progesterone may provide greater therapeutic benefit than vaginal preparations; however, data are lacking to support this contention, and previous trials of alternative progesterone preparations (including intramuscular progesterone) have shown varying results.…”
Section: Discussionmentioning
confidence: 99%
“…We studied a vaginal preparation of progesterone, at a dose of 400 mg twice daily, and it is possible that the results with this regimen are not generalizable to patients receiving other doses and preparations. However, we chose this route to deliver a greater proportion of the drug to the biologically relevant site (i.e., the uterus), 13,14 and the dose used (400 mg twice daily) represents a dose at the top end of the therapeutic window. 15 Some researchers have suggested that intramuscular preparations of progesterone may provide greater therapeutic benefit than vaginal preparations; however, data are lacking to support this contention, and previous trials of alternative progesterone preparations (including intramuscular progesterone) have shown varying results.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal administration of ISMN has been shown to result in lower plasma levels with peak levels being achieved only after 6 hours or more [14]. However, vaginal ISMN is thought to have its effects on the cervix much earlier due to the direct transport of the ISMN from the vagina to the cervix [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Возможны четыре механизма «первичного прохож-дения прогестерона в матку» при интравагинальном использовании микронизированного прогестерона: 1) прямая диффузия через ткани [31]; 2) пассаж прогестерона через цервикальный ка-нал из влагалища в полость матки [32];…”
Section: почему эндометрий в протоколах стимуляции яич-ников часто явunclassified
“…[35] на экстирпированных матках, подключенных к перфузионной системе без рецир-куляции. Суть данного эксперимента сводилась к то-му, что производилась экстирпация матки с верхней третью влагалища.…”
Section: почему эндометрий в протоколах стимуляции яич-ников часто явunclassified